POST-TRANSPLANT HYPERGLYCEMIA IS ASSOCIATED WITH INCREASED RISK OF LIVER ALLOGRAFT REJECTION - Wallia, Amisha (2010)
BACKGROUND: Intensive glycemic control has been shown to positively impact outcomes in an intensive care setting. Whether this practice is beneficial after liver transplantation (LT) is not known. METHODS: A retrospective review of patients undergoing LT from 2/02-07/04 was conducted to analyze the association between peri-operative hyperglycemia and outcomes after LT. Covariates included pre-existing diabetes, mean glucose three months pre-LT, need for insulin drip post-LT, mean total glucose during the post-LT hospitalization, age, gender, type of transplant, and MELD score. Outcomes within one year of LT included rejection, infection, re-hospitalization, prolonged ventilation, and patient/graft survival. RESULTS: 113 LT and 31 liver-kidney recipients were included. By multivariate logistic regression adjusting for covariates, the rejection rate was significantly lower for patients with postoperative glucose levels < 200 mg/dL (n=114) vs. > 200 mg/dL (n=30) (OR 0.055, 95%CI [0.0154, 0.200], p<0.001). The need for prolonged ventilation was more common in patients with glucose < 200 vs. > 200 mg/dL (OR 4.30, 95%CI [1.284, 14.388], p=0.018). While other outcomes, infection, re-hospitalization, patient/graft survival, were not different among the glucose control groups, rejection was associated with increased re-hospitalizations and infections. CONCLUSION: Our data demonstrate an association between immediate post-transplant glycemic control and the development of subsequent rejection. Prospective trials investigating the effects of perioperative glycemic control on outcomes and morbidity after LT are warranted.